High wall shear stress-dependent podosome formation in a novel murine model of intracranial aneurysm - Lu, Jiayi; Dai, Mengjun; Yan, Yuanqing; McCullough, Louise D.; Rui, Yan-Ning; Xu, Zhen (Frontiers in Stroke, 2024)
High wall shear stress (HWSS) contributes to intracranial aneurysm (IA) development. However, the underlying molecular mechanisms remain unclear, in part due to the lack of robust animal models that develop IAs in a HWSS-dependent manner. The current study established a new experimental IA model in mice that was utilized to determine HWSS-triggered downstream mechanisms. By a strategic combination of HWSS and low dose elastase, IAs were induced with a high penetrance in hypertensive mice. In contrast, no IAs were observed in control groups where HWSS was absent, suggesting that our new IA model is HWSS-dependent. IA outcomes were assessed by neuroscores that correlate with IA rupture events. Pathological analyses confirmed these experimental IAs resemble those found in humans. Interestingly, HWSS alone promotes the turnover of collagen IV, a major basement membrane component underneath the endothelium, and the formation of endothelial podosomes, subcellular organelles that are known to degrade extracellular matrix proteins. These induced podosomes are functional as they degrade collagenbased substrates locally in the endothelium. These data suggest that this new murine model develops IAs in a HWSS-dependent manner and highlights the contribution of endothelial cells to the early phase of IA. With this model, podosome formation and function was identified as a novel endothelial phenotype triggered by HWSS, which provides new insight into IA pathogenesis.